A Survey of Seasonal Gastrointestinal Parasitic Infections in Donkeys from a Semiarid Sub-Saharan Region, Sudan. (19th May 2016) - Ismail, Ahmed Abdurhman; Ahmed, Nasredin Khogali; Bashar, Ahmed Elhag; Seri, Hisham Ismail; El Tigani-Asil, El Tigani Ahmed; Abakar, Adam Dawoud
Abstract : Out of 92 donkeys examined for gastrointestinal parasites, 90 animals were found infected by one or more gastrointestinal parasites with an overall prevalence rate of 97.78%. The distributions of the recovered parasites in the different parts of the body were as follows: stomach, 92.4%, small intestine, 19.6%, caecum, 88%, colon, 80.4%, rectum, 73.9%, and cranial mesenteric artery, 64.1%. A significant difference was found between mean parasite counts and seasons. Hot wet season had higher mean parasites count (5411.5 ± 1694.4 ) in comparison with hot dry (1795.9 ± 399.6 ) and cool dry (1719.9 ± 522.4 ) seasons. Although there was no significant difference between age and mean parasite count, animals more than four years old had high mean count (3361.3 ± 921.8 ) in comparison with2330 ± 744.3 and2030.2 ± 873.1 for young and adults animals, respectively. No significant positive or negative correlation was found between total parasite counts of infected animals and any of the climatic factors. The parasites identified were Habronema spp. (40.2%), Trichostrongylus axei (30.4%), Parascaris equorum (18.5%), Anoplocephala perfoliata (4.35%), Gastrodiscus aegyptiacus (8.7%), large strongyles (84%), small strongyles (72%), and Oxyuris equi (1.1%).